Effects of free fat grafting on the prevention of Frey's syndrome and facial depression after parotidectomy: A prospective randomized trial. (9th October 2015) - Wang, Shaoxin; Li, Ling; Chen, Jin; Li, Xiaoxia; Yin, Jun; Liu, Kun; Li, Chunhua; Wang, Zhaohui; Li, Chao; Zhu, Guiquan
Abstract : Objectives/Hypothesis: To evaluate the effectiveness of free fat grafting in preventing Frey's syndrome (FS) and facial depression after parotidectomy compared with acellular dermis. Methods: A prospective randomized trial was performed. Patients who underwent parotidectomy were randomly assigned to abdominal free fat or acellular dermis grafting groups. The occurrence of FS, the aesthetic outcome, economic results, and other complications were evaluated. Results: Both acellular dermis and free fat grafts were effective in preventing FS with an equal rate of postoperative complications. Patients undergoing free fat grafting had a significantly higher aesthetic score and lower cost than those undergoing acellular dermis grafting. Conclusion: Free fat grafting has equal risks but more advantages compared with acellular dermis. Free fat grafting is an effective, convenient, and inexpensive option for parotidectomy defect reconstruction. Level of Evidence: 1b. Laryngoscope, 126:815–819, 2016